CLINICAL CHARACTERISTICS OF ENDOMETRIOSIS PHENOTYPES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents a detailed clinical analysis of various phenotypes of endometriosis, a chronic gynecological disease characterized by the presence of endometrial-like tissue outside the uterus. The study examines the specific clinical manifestations, diagnostic criteria, and progression patterns of different phenotypes, including superficial peritoneal, ovarian, and deep infiltrating endometriosis. Attention is paid to the correlation between phenotypic diversity and disease severity, as well as treatment response. The findings highlight the importance of phenotype-oriented diagnostics and personalized therapeutic approaches in improving patient outcomes.